Nilai-Nilai Indigenous Bali dalam Praktik Konseling Multikultural - Budiasa, I Nyoman; Hajaroh, Mami; Eliasa, Eva Imania; Azizah, Nur; Siswoko, Heri (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Multicultural cultural values are a strong foundation to be believed and important in the development of the world of Guidance and Counseling, especially in multicultural counseling practices. The cultural diversity that exists in Indonesia is very appropriate when counselors are able to explore and implement cultural values in counseling practices. One of the cultural values that can be used is to combine the concept of Balinese cultural values based on the beliefs of ancestors since ancient times which are religious through stories and meanings implied from generation to generation in the use of Tridatu thread bracelets and provide a special feel, especially for Hindus. The research method used is a qualitative description method by collecting library data, reading and recording and processing research materials then presenting them and drawing conclusions from the data obtained regarding the use of the Tridatu Bracelet. The thread used for Tridatu is not an ordinary thread. Before being given to the people, the thread has certainly gone through a ritual process first so that it has a deep meaning and philosophy. Hindus believe that the Tridatu Bracelet has the power of God Hyang Almighty as the creator, maintainer, and smelter. Counselors as implementers of counseling must really have an awareness of the cultural diversity that exists. Then the counselor should have good competence in multicultural coverage, namely awareness, knowledge and skills.